Modelling the contribution of teachers’ perceived school climate to foreign language teaching enjoyment - Tong Chu; Chentian Lv; Wanyong Wang (Humanities & Social Sciences Communications)
Abstract The increasing prevalence of language teacher depression and burnout has highlighted the urgent need to examine factors that support educators’ psychological well-being. Given this situation, Foreign Language Teaching Enjoyment (FLTE) has gained recognition as a key protective factor, shedding light on how emotional experiences can help improve teachers’ work performance. Grounded in an ecological perspective, this study focused on the investigation of a crucial influencing factor that shapes FLTE—perceived school climate—among 365 English as a Foreign Language (EFL) teachers in China. Using Structural Equation Modelling (SEM), the research evaluated the differential contributions of three dimensions of school climate: Teacher-Student Relationship, Instructional Innovation, and Decision Making. Findings indicated that both Teacher-Student Relationship and Instructional Innovation were significant predictors of FLTE, with Teacher-Student Relationship demonstrating the strongest predictive power. In contrast, Decision Making was not found to remarkably predict FLTE. These results highlighted the role of immediate, micro-level interactions in shaping teachers’ emotional experiences, while deemphasising the influence of the macro-level institutional factors. This study provided further practical implications to advocate for prioritising teacher-student rapport and innovative pedagogical practices. It also called for effective administrative strategies that can cultivate supportive, emotionally sustainable school environments.